ON THE EFFECT OF WOVEN GLASS FABRIC ORIENTATIONS ON WEAR AND FRICTION PROPERTIES OF POLYESTER COMPOSITE - YOUSIF, B. F.; EL-TAYEB, N. S. M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In this work, tribological investigations on the neat polyester (NP) and woven (600 g/m(2))-glass fabric reinforced polyester (WGRP) composite were carried out. Friction and wear characteristics of the WGRP composite were measured in three principal orientations, i. e., sliding directions relative to the woven glass fabric (WGF) orientations in the composites. These are longitudinal (L), transverse (T), and parallel (P) orientations. The experiments were conducted using a pin-on-disc (POD) machine under dry sliding conditions against a smooth stainless steel counterface. Results of friction coefficient and wear resistance of the composites were presented as function of normal loads (30 -100 N) and sliding distances (0.5 -7 km) at different sliding velocities, 1.7, 2.8, and 3.9 m/s. Scanning electron microscopy (SEM) was used to study the mechanisms of worn surfaces. Experimental results revealed that woven glass fabric improved the tribological performance of neat polyester in all three tested orientations. In L-orientation, at a low velocity of 1.7m/s, WGRP exhibited significant improvements to wear resistance of the polyester composite compared to other orientations. Meanwhile, at high velocities (2.8 and 3.9m/s), T-orientation gave higher wear resistance. SEM microphotographs showed different damage features on the worn surfaces, i. e., deformation, cracks, debonding of fiber, and microcracks.